Retinitis Pigmentosa Pathophysiology - o’g’li , Qo’ziyev Siddiqjon Rifat; Baxtiyorovna, Elmurotova Dilnoza (American Journal of Bioscience and Clinical Integrity, 2025)
Retinitis pigmentosa (RP) is a group of genetic eye disorders characterized by the progressive degeneration of photoreceptor cells in the retina, leading to vision loss. It typically begins with night blindness and gradually narrows the visual field, often resulting in tunnel vision. Mutations cause RP in various genes responsible for maintaining the health of photoreceptor cells, affecting their ability to respond to light. As RP advances, individuals may experience difficulty with tasks requiring peripheral vision, such as navigating in dimly lit environments or recognizing faces from a distance. Color vision can also be affected in some cases. While there is currently no cure for RP, ongoing research is exploring potential treatments and therapies to slow its progression or restore vision in patients with RP. Management often involves low-vision aids, orientation, and mobility training to help individuals adapt to their changing vision. This activity covers the underlying pathophysiology that produces dysfunction in the retina and the diagnostic measures, including an adequate physical exam and appropriate referral for expert evaluation.